21ST CENTURY CHALLENGES AND OPPORTUNITIES IN BUSINESS AND ENTREPRENEURSHIP INSTRUCTIONAL DELIVERY IN PUBLIC UNIVERSITIES IN ENUGU STATE, NIGERIA (NAU Journal of Technology and Vocational Education, 2025)
The paper focused on the challenges and opportunities facing educators of business and entrepreneurship education in using instructional delivery in public universities in South-East Nigeria. The study adopted descriptive survey design. The population of the study comprised 46 business and entrepreneurship Educators in public universities in Enugu State, Nigeria. Two research questions were raised for the study and two null hypotheses were tested at 0.05 level of significance. A structured questionnaire was used to seek the opinion of business and entrepreneurship education lecturers on the subject matter. The internal consistency of the instrument was established using Cronbach Alpha formula which yielded correlation co-efficient of 0.85 and 0.79 for clusters B1 to B2 with an overall reliability index of 0.82 obtained. Research questions were analyzed using mean and standard deviation while t-test was used to test the null hypotheses. Consequently, the study identified 10 challenges facing business educators in instructional delivery at 21st public universities in Enugu State, Nigeria. Also, there was no significant difference between the mean responses of male and female business educators on the challenges in the instructional delivery within entrepreneurship education curriculum at 21st public universities in Enugu State, Nigeria. Based on the findings of the study, the researchers recommended that National Universities Commission (NUC) and curriculum planners should ensure the integration of 21st-century teaching tools and pedagogies into the business and entrepreneurship education curricula.
Keywords: Challenges; Business education; Entrepreneurship education; Public universities